Different patterns of boundaries between Roma and non-Roma neighbourhoods - Tünde Virág (European Regional Science Association (ERSA), 2014)
Different patterns of boundaries between Roma and non-Roma neighbourhoods Virág Tünde HAS Centre for Economic and Regional Studies, Institute for Regional Studies, Budapest G_S Social segregation, poverty, and social policy in space According to various sociological surveys, every fifth Roma lives in segregated neighbourhoods, and out of them every third lives in small towns. Small towns have been described as places, where differing patterns of segregation and the separation between Roma and non-Roma people appear in a most diversified manner. In my view the status of various parts of the towns, referred to as `segregated' in the development documents and in the narratives of policy makers, is not fixed, but, rather, continually changes, and reflects the relation of townspeople and leaders of local community to poor people and various ethnic groups. In other words, wherever majority society is still stable and has enough resources to uphold the spatial, social and institutional segregation of the Roma, it will continue to do so in most cases, and it will exactly regulate which parts of the settlement the Roma can move in. Whether the Roma families in the settlement live concentrated in one neighbourhood or in several locations of various status and public perception reflects the degree of separation and the different needs of Roma and non-Roma for segregation, as well as the difference among the various groups of Roma. Based on that, we can establish the existence of sharp physical or/and mental boundaries within the settlements, enclosing the segregated Roma neighbourhood within a given settlement; or blurred boundaries separating such a neighbourhood from the rest of the settlement. The degree of sharpness of separation is mostly influenced by (1) whether a newly segregated neighbourhood was formed during the seventies' programme to eliminate Roma ghettos; (2) how layered the local Roma society is; (3) whether economic co-operation or social contacts exist between Roma and the non-Roma. The boundaries between the two groups were either relaxed or fixed by the realisation (or the lack thereof) of intensive development programmes and infrastructural subsidies targeting the alleviation of poverty.
Keywords: 330; ethnic boundaries; Roma; small town